An Activity‐Based Sensing Approach for the Detection of Cyclooxygenase‐2 in Live Cells. Issue 8 (6th February 2020) - Yadav, Anuj K.; Reinhardt, Christopher J.; Arango, Andres S.; Huff, Hannah C.; Dong, Liang; Malkowski, Michael G.; Das, Aditi; Tajkhorshid, Emad; Chan, Jefferson
Abstract: Cyclooxygenase‐2 (COX‐2) overexpression is prominent in inflammatory diseases, neurodegenerative disorders, and cancer. Directly monitoring COX‐2 activity within its native environment poses an exciting approach to account for and illuminate the effect of the local environments on protein activity. Herein, we report the development of CoxFluor, the first activity‐based sensing approach for monitoring COX‐2 within live cells with confocal microscopy and flow cytometry. CoxFluor strategically links a natural substrate with a dye precursor to engage both the cyclooxygenase and peroxidase activities of COX‐2. This catalyzes the release of resorufin and the natural product, as supported by molecular dynamics and ensemble docking. CoxFluor enabled the detection of oxygen‐dependent changes in COX‐2 activity that are independent of protein expression within live macrophage cells. Abstract : Activity‐based sensing of COX‐2 : An isoform‐selective fluorogenic probe reports on enzymatic activity within live cells. A two‐step activation facilitates the release of the natural product and resorufin for confocal imaging and flow cytometry. CoxFluor indicates that COX‐2 activity can be regulated by oxygen without a change in the protein expression level.